The impact of fluctuation of oil price towards Malaysian economy / Amira Aisyah Jamari - Jamari, Amira Aisyah (2018)
As Southeast Asia's biggest Energy Department maker and purchaser, Malaysia which is the net oil exporter and Southeast Asia's second biggest vitality maker behind Republic of Indonesia. This study examines the impact of fluctuation of oil price toward economic in Malaysia by using the data that been collected from the World Bank Data from the year 1984 till 2014 which is for 30 years. An analysis using Ordinary Least Square, Granger and some diagnostic checks techniques that include serial correlation, heteroskedasticity, multicollinearity and Ramsey test. Overalls of the results show the positive reaction towards the growth of real oil prices. As conclusion, the fluctuation of the oil price is positively significant towards Malaysian economy which includes of GDP, exchange rate and net export. However, since these studies is only focus on the short-run, therefore based on the grangers results has shown that there is a one way of relationship between changes on oil price towards exchange rate and GDP in Malaysia. In the same meaning, the variable of exchange rate and GDP can be affected by the fluctuation of the oil prices. These result shows that both variable was affecting the growth of Malaysia in the shortrun. However, since the overall conclusions show the positive significant results, growth of the oil prices is less impactful on the Malaysian Ringgit.